Students’ Perception on E-Learning – A Study of Online Certificate Courses - Kalyanasundaram, P.; Madhavi, C. (International Journal of Psychosocial Rehabilitation, 2024)
With the advent of development in information and communication technology, higher education institutions are turning their attention towards course offerings in the online mode. With the opportunities and challenges, organizations are seeking to understand the perspective of the learners. This paper attempts to study the perception of learners of value added courses offered to students. Eight certificate courses like Forex Management, Operations Research, Medical Law and Genetics, etc. were offered as an add-on value added courses during the graduation through online mode and student perceptions were studied with regard to usability, user friendliness, course content, test friendliness etc. Results show that students who embraced online learning felt positive about elearning.